Law Enforcement Against Criminal Acts of Using Other People's Voting Rights in Elections - Zefrizal Zefrizal (International Journal Reglement & Society (IJRS), 2022)
Election law issues can be said to be more complex. In addition to the many categories of problems, the implementation of handling election legal issues also involves many institutions/institutions. The type of research used in this research is normative juridical. The nature of this research is descriptive analytical. As for what is meant by descriptive analytical research is a research that can describe in detail and systematically about the object under study. Secondary legal materials include explanations of primary legal materials in the form of expert doctrine found in books, journals, and websites. The results of the study show that the provisions of Article 533 of Law Number 7 of 2017 concerning General Elections state that